Islamic Character Education Management in Developing the Empathy Values for Students of State Islamic University of Sunan Kalijaga Yogyakarta - Na’imah, Na’imah (Dinamika Ilmu: Jurnal Pendidikan, 2018)
This study of the management of Islamic character education is the basis for developing the value of empathy for students of the Faculty of Science of Islamic Education and Teacher Training, Sunan Kalijaga State Islamic University Yogyakarta. Students must get education not only scientifically through Islamic character to develop their empathy values. This noble personality needs to be possessed by students. This is to create a comfortable, harmonious, pleasant atmosphere of life both when students are in the campus environment and off campus. This study uses a qualitative research model, to analyze the character of student empathy through Islamic education management studies based on questionnaires, observation, documentation, and interviews, and inductive analysis. The results of the Islamic character education management study show that students of the Tarbiyah and Teacher Training Faculty of the State Islamic University of Sunan Kalijaga Yogyakarta have a fairly good empathy character, which is assessed based on seven indicators of empathy. The most dominant empathy attitude of the student (83%) is the attitude of appreciation of other people who have done something correctly and the smallest (69%) done by the student is perception of others.